Understanding a trapezoid and how to find the area takes some basic background in math but is not so complex that it is out of reach of any logically thinking individual. First you will need to write out the equation to find the area of a trapezoid: Area=height(b1+b2) / (2), you can then re-arrange the equation to determine the unknown base or height.

To find the measure of missing base, you multiply 1/2 times height, and then divide each side by that product. Canceling the 1/2*h on one side, leaving you with area over half the height equal to b1 + b2. You then subtract b1 from each side, which results in the following equation: (area / (1/2*h)) - b1 = b2.

As an example set of numbers, let's say area = 36; height = 4; and b1 =8. We need to find b2.

When we substitute in to the original equation, it looks like this:

Substitution: 36 = 1/2*(4) (8 + b2)

Divide both sides by 1/2 height: 36/2 = (8 + b2)

Subtract b1 from both sides: 18 - 8 = b2

Simplify: 10 = b2

The measure of the missing base in this example is 10.

When properly re-arranging the equation to solve for the missing height the equation becomes: Height= 2Area/(b1+b2).

When we substitute in to the original equation, it looks like this:

If the area is 30 and b1 is 4 and b2 is 6, then the equation can be written as "Height = 2 x 30/(4+6). Multiply 2 by 30 and you get 60. Add 4 and 6 to get 10. Divide 60 by 10 to solve for the height. In this example, the measure of the missing height is 5.

Take a few minutes and put these on paper, see how you do at solving a few examples. Once you get the hang of the equations it’s not as hard as it appears.

To find the measure of missing base, you multiply 1/2 times height, and then divide each side by that product. Canceling the 1/2*h on one side, leaving you with area over half the height equal to b1 + b2. You then subtract b1 from each side, which results in the following equation: (area / (1/2*h)) - b1 = b2.

As an example set of numbers, let's say area = 36; height = 4; and b1 =8. We need to find b2.

When we substitute in to the original equation, it looks like this:

Substitution: 36 = 1/2*(4) (8 + b2)

Divide both sides by 1/2 height: 36/2 = (8 + b2)

Subtract b1 from both sides: 18 - 8 = b2

Simplify: 10 = b2

The measure of the missing base in this example is 10.

When properly re-arranging the equation to solve for the missing height the equation becomes: Height= 2Area/(b1+b2).

When we substitute in to the original equation, it looks like this:

If the area is 30 and b1 is 4 and b2 is 6, then the equation can be written as "Height = 2 x 30/(4+6). Multiply 2 by 30 and you get 60. Add 4 and 6 to get 10. Divide 60 by 10 to solve for the height. In this example, the measure of the missing height is 5.

Take a few minutes and put these on paper, see how you do at solving a few examples. Once you get the hang of the equations it’s not as hard as it appears.